Pendidikan Islam: Bagaimana Pengaruhnya dalam Membentuk Karakter Mahasiswa yang Bertanggung Jawab dalam Menegakkan Hukum di Kampus? - Damayanti, Alif; Maulidina, Annisa; Moniaga, Friska Valentina; Munawaroh, Siti Rahma; Suresman, Edi (Darul Yasin Al Sys, 2024)
The aim of this research is to examine and analyze the influence of Islamic religious education on the formation of student character who is responsible for upholding the law in the campus environment. Quantitative methods are the type of method used in this research. The independent variable (X) in this research is Islamic religious education and the dependent variable (Y) in this research is the student's character in upholding the law. The population in this study were students from the Faculty of Economics and Business Education, Indonesian Education University, class 2022-2023 with a sample of 72 students. Data analysis was carried out using linear regression analysis techniques. Based on validity and reliability tests, the instruments used for data collection show that the instruments are valid and reliable. Based on the hypothesis test, it is known that the calculated t of 10.335 is greater than the t table of 1.66691 and the calculated F result of 106.805 is greater than the F table of 3.89, and the significance result of 0.000 is less than 0.05. The results of this research show that there is a positive and significant influence of Islamic religious education on the character of students who are responsible for enforcing the law in the campus environment.